Synergistic effect of carbon emission reduction from regional carbon trading on air pollutant emission reduction - Yu, Qiuli; Yang, Shengyi (Frontiers in Environmental Science, 2025)
IntroductionIn recent years, with the intensification of climate change, reducing greenhouse gas emissions has become a necessary measure to address climate change. The carbon trading policy, as an effective policy to promote carbon reduction, has been accepted and implemented by many countries.MethodThis study employs the twofold difference approach and synthetic control method to evaluate the impact of carbon trading policies on air pollutant emissions.ResultResults showed that implementing carbon trading could lead to an average reduction of 54.13 million tonnes of CO2 annually, alongside decreases of 176.1 thousand tonnes of SO2 and 112.5 thousand tonnes of NOx. Among the six pilot regions—Hubei, Guangdong, Shanghai, Beijing, Tianjin, and Chongqing—Hubei exhibited the most significant CO2 reduction, approximately 66.25 million tonnes. Hubei and Beijing also showed notable synergistic effects for SO2 reduction. The synergistic emission reduction effect of NOx was more evident in Chongqing, Shanghai, and Hubei.DiscussionThese findings highlighted the effectiveness of carbon trading in mitigating CO2 and related air pollutants. To enhance and optimize the carbon trading market, the study recommends increasing the clean energy share in the energy mix, improving market management systems, enforcing reasonable penalties for defaults, and developing tailored carbon trading mechanisms for different industries.